DEVELOPMENT OF DIAGNOSTIC ALGORITHM OF ORAL FLUID BIOMARKERS FOR EARLY DIAGNOSE OF PERIODONTAL DISEASES (Uz Conferences, 2025)
It is known that periodontitis is a multifactorial chronic irreversible inflammatory disease that affects the supporting structures of the teeth, initiated and spread by a complex interaction between periopathogens and the host’s immune system. It begins with a microbial infection, followed by periodontal tissue damage caused by leukocyte hyperactivity, cytokines, eicosanoids, and matrix metalloproteinases. Based on the assessment of their diagnostic properties, the most informative laboratory biomarkers of oral fluid microflora, proteolytic enzymes cathepsin, elastase, haptoglobin, IL-1, IL-6, IL-8, and TNF-α were determined in gingivitis and chronic periodontitis. It allows to evaluate the diagnostic efficiency of these markers in patients with periodontal diseases and to use them for early diagnosis in non-invasive diagnostics. According to the results of our research, the markers change sequentially in different stages of periodontitis, so the combination of biomarkers gives a more effective result for the diagnosis of the disease state [3].